Neurorrafia do ramo bucal dorsal do nervo facial em coelhos com proteção de segmento intestinal alógeno - Busnardo, Camila Araújo; Eurides, Duvaldo; Beletti, Marcelo Emílio; Baungarten, Letícia Binda; Guimarães, Ednaldo Carvalho; e Silva, Frederico Ozanan Carneiro; Alves, Lorena Borges; de Oliveira, Benito Juarez Nunes Alves; de Souza, Luis Augusto; da Silva, Luiz Antônio Franco; Daleck, Carlos Roberto [UNESP] (My University, 2009)
18 rabbits, New Zealand, males, adults were used for clinical and histological evaluation of repair dorsal buccal branch of facial nerve after 15, 30 and 60 days postoperatively (PO). The animals were divided into two groups for transection and 10-0 nylon monofilament epineural suture of buccal branch. In animals in Group I, the nerve was coated with protection of jejunum allograft preserved in glycerin 98% and in group II was applied epineural suture. Both groups occurred the return of movement of the upper lip from the eighth week. There was infiltrated cellular and giant cells with fibrosis unsystematic and collagen fibers of the allograft jejunum joing to the connective tissue. At 15 and 30 days of PO, the distal nerve stumps of both groups were found with degeneration wallerian and in 60 days, regenerated fibers. The repair of the dorsal buccal branch of facial nerve with the allograft wasn't significantly different between the control rabbits as to the assessment of histological and functional recovery.
Neurorrhaphy of the dorsal buccal branch of facial nerve in rabbits with protection of allograft intestinal segment
Keywords: Graft; Intestine; Nerve regeneration; Peripheral nerve; Animalia; Oryctolagus cuniculus; Walleria